Isolation and Functional Analysis of Human Neutrophils. (2nd November 2015) - Kuhns, Douglas B.; Priel, Debra A. Long; Chu, Jessica; Zarember, Kol A.
Abstract: This unit describes the isolation of human polymorphonuclear neutrophils (PMN) from blood using dextran sedimentation and Percoll or Ficoll‐Paque density gradients. Assays of neutrophil functions including respiratory burst activation, phagocytosis, and microbial killing are also described. © 2015 by John Wiley & Sons, Inc.